Enhanced photothermal therapy of biomimetic polypyrrole nanoparticles through improving blood flow perfusion. (October 2017) - Wang, Xuejun; Li, Haichun; Liu, Xianping; Tian, Ye; Guo, Huishu; Jiang, Ting; Luo, Zimiao; Jin, Kai; Kuai, Xinping; Liu, Yao; Pang, Zhiqing; Yang, Wuli; et al.
Abstract: In this study, we reported a strategy to improve delivery efficiency of a long-circulation biomimetic photothermal nanoagent for enhanced photothermal therapy through selectively dilating tumor vasculature. By using a simply nanocoating technology, a biomimetic layer of natural red blood cell (RBC) membranes was camouflaged on the surface of photothermal polypyrrole nanoparticles (PPy@RBC NPs). The erythrocyte-mimicking PPy NPs inherited the immune evasion ability from natural RBC resulting in superior prolonged blood retention time. Additionally, excellent photothermal and photoacoustic imaging functionalities were all retained attributing to PPy NPs cores. To further improve the photothermal outcome, the endothelin A (ETA ) receptor antagonist BQ123 was jointly employed to regulate tumor microenvironment. The BQ123 could induce tumor vascular relaxation and increase blood flow perfusion through modulating an ET-1/ETA transduction pathway and blocking the ETA receptor, whereas the vessel perfusion of normal tissues was not altered. Through our well-designed tactic, the concentration of biomimetic PPy NPs in tumor site was significantly improved when administered systematically. The study documented that the antitumor efficiency of biomimetic PPy NPs combined with specific antagonist BQ123 was particularly prominent and was superior to biomimetic PPy NPs ( P < 0.05) and PEGylated PPy NPs with BQ123 ( P < 0.01), showing that the greatly enhanced photothermal treatment could be achieved with low-dose administration of photothermal agents. Our findings would provide a promising procedure for other similar enhanced photothermal treatment by blocking ETA receptor to dramatically increase the delivery of biomimetic photothermal nanomaterials.